Redescription of a Hymenostome Ciliate, Tetrahymena setosa (Protozoa, Ciliophora) Notes on its Molecular Phylogeny. (7th September 2018) - Pan, Mengmeng; Wang, Yurui; Yin, Haiwei; Pan, Xuyue; Mu, Weijie; Al‐Rasheid, Khaled A. S.; Fan, Xinpeng; Pan, Xuming
Abstract: In recent years, Tetrahymena species have been used as model organisms for research in a wide range of fields, highlighting the need for a fuller understanding of the taxonomy of this group. It is in this context that this paper uses living observation and silver staining methods to investigate the morphology and infraciliature of one Tetrahymena species, T. setosa (Schewiakoff 1892 Verh. Naturh. Med. Ver. Heidelb ., 4:544) McCoy (1975) Acta Protozool ., 14:253; the senior subjective synonym of T. setifera Holz and Corliss (1956) J. Protozool ., 3:112; isolated from a freshwater pond in Harbin, north‐eastern China. This organism can be distinguished from other described Tetrahymena species mainly by its single caudal cilium, which is about twice the length of the somatic ciliature. While the Harbin isolate appears similar to the population described by Holz and Corliss (1956) J. Protozool ., 3:112, an improved diagnosis for T. setosa is given based on the previous descriptions and the Harbin population. In summary, this species can be recognized mainly by the combination of the following characters: body in vivo approximately 40 μm × 25 μm, 21–26 somatic kineties, one to four contractile vacuole pores associated with meridians 6–11 and a single caudal cilium. The small subunit ribosomal (SSU) rRNA gene and the cox1 gene sequences of Harbin population are also characterized in order to corroborate that the isolated species branches in phylogenetic trees as a T. setosa species. The phylogenetic analysis also indicated that sequences of populations of Tetrahymena species should be published with detailed morphological identifications.